A self-consistent approach to calculate the electronic structure of disordered alloys - Yildiz, AK; Tatar, C (Elsevier Science Bv, 2002)
In this study, a theoretical method proposed earlier is used for calculating the electronic states in disordered alloys. The method developed by Beeby for structurally disordered systems is applicable to lattices consisting of substitutional disordered alloys in any dimensionality. The application to some binary and ternary disordered alloys having face-centred cubic and body-centred cubic lattice are introduced within the tight-binding approximation. Some illustrative results are presented and compared with the expected results obtained from some available methods. It is found that the method is computationally very simple and gives densities of states that agree with the expected results. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: disordered alloys; density of states; substitutional alloys; self-consistent